Tourism-Energy-Environment-Growth Nexus: Evidence from India - MISHRA, P. K.; ROUT, Himanshu B.; KESTWAL, Ashish K. (Journal of Environmental Management and Tourism, 2019)
This paper examined the dynamic linkages between tourism development, energy consumption, environmental degradation and economic growth in the context of the Indian economy. The short-run findings establish a chain-link between tourism development, economic growth, energy consumption and environmental degradation. Foreign tourist arrivals positively contribute to economic growth which in turn increases per capita energy use thereby raising CO 2 emissions – a major cause of environmental degradation and consequential adverse effects on tourism development. The long-run findings, although inconclusive, are only indicative of short-run observations. Therefore, the policy focus should be on devising promotional strategies for encouraging the extensive use of clean energy for environmental protection. Such a policy base can be instrumental in fostering the development of India tourism and also, be pivotal for achieving sustainable economic growth.